Insilico Identification Of Preferred Amino Acids For Selective Binding Of D-Neup5ac - MANDAGE RAJENDRA HARIBHAU; WADNERKAR AMOL SHRIRAM (International Journal of Pharma and Bio Sciences, 2010)
A statistical analysis of the carbohydrate–protein interaction in the PDB was carried out to investigate sequential aspects of the amino acids that are preferred for the selective binding of N-acetyl-D-neuraminic acid (D-Neup5Ac) chain. 2264 amino acids from 106 protein sequences were analysed in the vicinity of 277 Neup5Ac residues using GlyVicinity. Within a distance of 4 A° in vicinity of D-Neup5Ac, polar amino acids are more frequently observed as compare to other amino acids. There is a high frequency of occurrence of tyrosine, serine, asparagine, arginine residues in the vicinity of D-Neup5Ac chain whereas cysteine is the rarest amino acid found in protein–carbohydrate interaction. The positional preference of certain potential amino acids in vicinity of Neup5Ac residues has been discussed in terms of absolute counts, percentage, and deviations from natural abundances. This analysis provides a basis for further studies on the molecular mechanism of carbohydrate–protein interaction.